Absolute configuration of the antimalarial erythro-mefloquine – vibrational circular dichroism and X-ray diffraction studies of mefloquine and its thiourea derivative. Issue 85 (26th August 2016) - Kohout, M.; Vandenbussche, J.; Roller, A.; Tůma, J.; Bogaerts, J.; Bultinck, P.; Herrebout, W.; Lindner, W.
Abstract : The long-standing discussion of the absolute configuration of erythro -mefloquine is revisited, showcasing the strength of a combination of experimental and calculated vibrational circular dichroism spectroscopy. Abstract : The long-standing discussion of the absolute configuration of erythro -mefloquine is revisited, showcasing the strength of a combination of experimental and calculated vibrational circular dichroism spectroscopy. The resulting assignment of one of the most important antimalarials is subsequently confirmed by electronic circular dichroism spectroscopy and X-ray diffraction-based structure elucidation of thiourea derivatives, adding to the amount of evidence on the absolute configuration that had long remained a matter of debate.